Count on dopamine: influences of COMT polymorphisms on numerical cognition - Júlio-Costa, Annelise; Antunes, Andressa M.; Lopes-Silva, Júlia B.; Moreira, Bárbara C.; Vianna, Gabrielle S.; Wood, Guilherme; Carvalho, Maria Raquel S.; Haase, Vitor G. (Frontiers in Psychology, 2013)
Catechol-O-methyltransferase (COMT) is an enzyme that is particularly important for the metabolism of dopamine. Functional polymorphisms of COMT have been implicated in working memory and numerical cognition. This is an exploratory study that aims at investigating associations between COMT polymorphisms, working memory and numerical cognition. Elementary school children from 2th to 6th grades were divided into two groups according to their COMT val158met polymorphism (homozygous for valine allele [n= 61] versus heterozygous plus methionine homozygous children or met+ group [n=94]). Both groups were matched for age and intelligence. Working memory was assessed through digit span and Corsi blocks. Symbolic numerical processing was assessed through transcoding and single-digit word problem tasks. Non-symbolic magnitude comparison and estimation tasks were used to assess number sense. Between-group differences were found in symbolic and non-symbolic numerical tasks, but not in working memory tasks. Children in the met+ group showed better performance in all numerical tasks while val homozygous children presented slower development of non-symbolic magnitude representations. These results suggest COMT-related dopaminergic modulation may be related not only to working memory, as found in previous studies, but also to the development of magnitude processing and magnitude representations.